Social support mediates social frailty with anxiety and depression - Yang Liu; Mengjiao Yang; Yangyang Zhao; Ziwei Wang; Jie He; Yali Wang; Tokie Anme (BMC Pulmonary Medicine, 2024)
Abstract Background Anxiety and depression are prevalent comorbidities in patients with chronic obstructive pulmonary disease (COPD). However, existing research has yielded conflicting findings regarding the effects of social frailty on anxiety and depression. The primary aim of this study is to validate the relationship between social frailty and social support with anxiety and depression in patients with acute exacerbations of COPD (AECOPD) and to investigate whether social support could explain the variations in prior study outcomes for patients with AECOPD. Methods Of the 315 patients hospitalized with AECOPD at the respiratory intensive care unit of a large tertiary care institution in Sichuan Province of China, between August 2022 and June 2023 who were surveyed, 306 were included in the analysis after excluding missing data. We conducted a logistic regression analysis to examine the associations of social frailty and social support with anxiety and depression and performed mediation analyses to examine whether social support mediates the relationship of social frailty with anxiety and depression. Results The logistic regression analysis revealed that social frailty did not associate anxiety or depression in patients with AECOPD. The mediation analysis supported this idea and indicated that while social frailty does not directly influence anxiety or depression, it can through social support. Conclusions The findings suggest that while social frailty may not directly impact anxiety or depression in patients with AECOPD, social support plays a crucial mediating role. Enhancing social support can indirectly alleviate anxiety and depression among these patients. Enhancing social support networks should thus be prioritized by healthcare providers and family members to improve mental health outcomes in this patient population.